Experiences of Head and Neck Cancer Patients in Middle Adulthood: Consequences and Coping - Kathryn Grattan; Catherine Kubrak; Vera Caine; Dan A. O’Connell; Karin Olson (Global Qualitative Nursing Research, 2018)
The head and neck cancer (HNC) rate is rising among the middle-aged adult population. This trend has been attributed primarily to human papillomavirus exposure. An HNC diagnosis and its complex treatments may trigger life-changing physical, emotional, and social consequences. An interpretive descriptive study was conducted to describe the experiences of a purposive sample of 10 middle-aged adults who had experienced HNC. Two main themes were identified: consequences of HNC and coping with HNC. Subthemes of consequences of HNC included: voicelessness; being or looking sick; shifts in family dynamics; and sexual practices, sexual feelings, and stigma. Subthemes of coping with HNC included seeking information, discovering inner strengths, relying on a support network, establishing a sense of normalcy, and finding meaning within the experience. Supportive nursing interventions were identified by considering results from the standpoint of King’s theory of goal attainment.